2018
DOI: 10.1007/s13300-018-0396-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Patterns of Glucagon-Like Peptide-1 Receptor Agonists in Patients with Type 2 Diabetes Mellitus in Italy: A Retrospective Cohort Study

Abstract: IntroductionReal-world evidence on glucagon-like peptide-1 receptor agonist (GLP-1 RAs) usage is emerging in different European countries but is lacking in Italy. This retrospective cohort study aimed to describe the real-world drug utilization patterns in patients initiating GLP-1 RAs for treating T2DM in Italy.MethodsAdults aged ≥ 20 years and with ≥ 1 oral antidiabetic drug (alone or in combination with insulin) other than GLP-1 RAs in the 6 months prior to initiating exenatide twice daily (exBID), exenatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
3
29
1
Order By: Relevance
“…6,7 Literature suggests patients are more likely to adhere to injectable medications administered weekly rather than daily. [8][9][10][11] Clinical outcomes of HbA 1c reduction and weight loss seen in the present study were similar or better than those demonstrated in clinical trials that led to the approval of GLP-1 receptor agonists. The LEAD trials for liraglutide found 1.0%-1.5% reductions in HbA 1c and weight loss varied from 0.2-3.2 kg.…”
Section: Discussionsupporting
confidence: 78%
“…6,7 Literature suggests patients are more likely to adhere to injectable medications administered weekly rather than daily. [8][9][10][11] Clinical outcomes of HbA 1c reduction and weight loss seen in the present study were similar or better than those demonstrated in clinical trials that led to the approval of GLP-1 receptor agonists. The LEAD trials for liraglutide found 1.0%-1.5% reductions in HbA 1c and weight loss varied from 0.2-3.2 kg.…”
Section: Discussionsupporting
confidence: 78%
“…A retrospective cohort analysis was conducted using IQVIA’s Real-World Data (RWD) Adjudicated Pharmacy Claims in Belgium, France, Germany, Italy, the Netherlands, and Canada. Data from these European countries were utilized in prior analyses by the authors, and these countries were selected to provide a broad representation of several countries in Europe [ 35 , 37 , 39 41 ]. The current analysis follows previously published methods [ 35 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study is an update of prior multi-country European analyses from the authors, incorporating more recent data and, specifically, the inclusion of patients treated with dulaglutide [ 35 , 40 ]. Recent analyses have also been completed by the authors in Italy and Germany, although with varied selection windows and follow-up periods [ 37 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…After excluding those not reporting poolable data for any of the three elected outcome measures and adding the results of the present study, we included in the meta-analysis 3 studies 13,14 reporting the change in HbA1c (6035 patients) and the change in body weight (9384 patients), and 8 studies [15][16][17][18][19][20][21] reporting discontinuation rates (110 232 patients). Follow-up duration was 6 months in 5 studies 14,16,17,20,21 and 12 months in the others. 13,15,18,19 Altogether, there was no difference between liraglutide and ExeOW for the change in HbA1c [0.01%; 95% confidence interval (CI) -0.08; 0.09; no heterogeneity, Figure 2B] or for the change in body weight (0.12 kg; 95% CI -0.26; 0.51; no heterogeneity, Figure 2C).…”
Section: Meta-analysismentioning
confidence: 99%